Leksikalsk beskrivelse af adverbiers semantik i norsk, svensk og dansk – LEXADV - Nimb, Sanni; Vadtvedt Fjeld, Ruth; Gronostaj, Maria Toporowska; Pedersen, Bolette Sandford (Nordiske Studier i Leksikografi, 2006)
A lexical semantic description of adverbs in Danish, Norwegian and Swedish – LEXADV. The LEXADV-project is a Scandinavian research project with the aim of extending the three Scandinavian semantic lexica building on the SIMPLE lexicon model with the word class of adverbs. In order to do so, a classification covering the many different meanings that adverbs can have, is established as well as a set of formal relations and features. In this paper we describe in detail the ontology and how three groups of adverbs are described in the lexicon, namely degree adverbs, time adverbs and modal adverbs. The formal description of each lemma is based on the definition in the recently published Danish dictionary Den Danske Ordbog. Afterwards the lemma is translated into Swedish and Norwegian and copies of the Danish lexical entry are created. Finally these copies are evaluated and adjusted to the target language if necessary. Some of the translation problems that arise during this process are discussed in the paper.